2019
DOI: 10.3390/nu12010085
|View full text |Cite
|
Sign up to set email alerts
|

Deacetyl Ganoderic Acid F Inhibits LPS-Induced Neural Inflammation via NF-κB Pathway Both In Vitro and In Vivo

Abstract: Microglia mediated neuronal inflammation has been widely reported to be responsible for neurodegenerative disease. Deacetyl ganoderic acid F (DeGA F) is a triterpenoid isolated from Ganoderma lucidum, which is a famous edible and medicinal mushroom used for treatment of dizziness and insomnia in traditional medicine for a long time. In this study the inhibitory effects and mechanisms of DeGA F against lipopolysaccharide (LPS)-induced inflammation both in vitro and in vivo were investigated. On murine microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Several studies have demonstrated that insulin resistance by IRS-1 and IRS-2 dysregulation in the brain causes onset of neurodegenerative disease and results in cognitive decline 54 , 56 . Serine phosphorylation of IRS-1 elevates amyloid beta accumulation and exacerbates memory deficit in AD brain 57 . In addition, insulin receptor knockout mice showed abnormal synaptic transmission and reduction of AKT signaling activation 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that insulin resistance by IRS-1 and IRS-2 dysregulation in the brain causes onset of neurodegenerative disease and results in cognitive decline 54 , 56 . Serine phosphorylation of IRS-1 elevates amyloid beta accumulation and exacerbates memory deficit in AD brain 57 . In addition, insulin receptor knockout mice showed abnormal synaptic transmission and reduction of AKT signaling activation 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Two major active components are responsible: G. lucidum polysaccharides and G. lucidum triterpenoids (GTs) [ 15 ]. As one of the most abundant GTs, ganoderic acids (GAs) have anti-inflammatory, anti-oxidative stress, anti-tumor and anti-apoptotic effects [ 16 , 17 , 18 , 19 ]. It has been reported that Ganoderic Acid F, one component of GAs, can suppress LPS-induced the activation of NF-kB pathway and inhibit LPS-triggered iNOS expression and the production and secretion of relative inflammatory cytokines in mice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most abundant GTs, ganoderic acids (GAs) have anti-inflammatory, anti-oxidative stress, anti-tumor and anti-apoptotic effects [ 16 , 17 , 18 , 19 ]. It has been reported that Ganoderic Acid F, one component of GAs, can suppress LPS-induced the activation of NF-kB pathway and inhibit LPS-triggered iNOS expression and the production and secretion of relative inflammatory cytokines in mice [ 16 ]. Therefore, we hypothesize that GAs can alleviate RIRI via inhibiting inflammatory response and cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…DeGA F inhibited mRNA expression of TNF-α , IL-6 , and IL-1β . Also, the pretreatment with DeGA F inhibited the protein expression of Akt, IKKα/β, and IκBα (which participate in the NFƙB activation), compared to the LPS-stimulated cells ( Sheng et al, 2019 ). Polysaccharides from G. lucidum have also been shown to inhibit LPS- and Aβ-induced pro-inflammatory levels of IL-1β, IL-6, and iNOS, and induce the expression of the anti-inflammatory cytokine TGFβ ( Cai et al, 2017 ).…”
Section: Introductionmentioning
confidence: 98%